Second trimester maternal serum inhibin-A in fetal anemia secondary to hemoglobin Bart's disease - Tongprasert F. (Informa Healthcare, 2014)
Objective: To compare the levels of inhibin-A between pregnancies with fetal anemia secondary to Hb Bart's disease and pregnancies with normal non-Anemic fetuses. Methods: Sixty-five pregnancies at risk of fetal Hb Bart's disease scheduled for cordocentesis at 18-22 weeks were prospectively recruited into the study. Inhibin-A levels were measured from maternal blood drawn before cordocentesis. Fetal blood samples were collected for fetal Hb typing and hemoglobin (Hb) levels. Results: Maternal serum inhibin-A was significantly higher in women with fetal Hb Bart's disease than those with unaffected fetuses (1.03MoM (multiple of median) and 0.75 MoM, respectively, p=0.001). The relationship between maternal serum inhibin-A and fetal Hb level was a quadratic equation; inhibin-A=5.248-9.415(Hb)+4.919(Hb)2 (r2=0.274, p<0.001). Maternal serum inhibin-A did not correlate with cardiomegaly but was significantly associated with placental thickness; inhibin-A=1.372-0.751(Pl) +0.214(Pl)2 (r2=0.237, p=0.007). Conclusions: Maternal serum inhibin-A levels were significantly higher in pregnancies with fetal Hb Bart's disease. The elevation of inhibin-A was likely to be a consequence of fetal anemia and placentomegaly. Since inhibin-A is commonly used as a component of quadruple test; the calculated risk of Down's syndrome may be unreliable in pregnancies with fetal Hb Bart's disease or possible fetal anemia. © 2014 Informa UK Ltd. All rights reserved: reproduction in whole or part not permitted.